India revisited : conversations on continuity and change - Jahanbegloo, Ramin; Thapar, Romila (New Delhi ; Oxford : Oxford University Press, 2008)
Ramin Jahanbegloo converses with 27 leading Indian personalities - social scientists, journalists, activists, artists, and sportspersons - to gain an understanding of contemporary Indian society. The book gives a one-of-a-kind view of contemporary India, seen through the eyes of those who have engaged with the country, her people, and culture through their work and lives.
Description based on print version record.
Keywords: India -- Civilization -- 21st century; India -- Social conditions -- 1947-; India -- Politics and government -- 1977-; India -- History -- 1947-; India -- Religion